Catalyst for purifying nitrogen oxide and method of producing catalyst for purifying nitrogen oxide

The AEI or AFX type zeolite catalyst with controlled copper and manganese content addresses thermal deterioration and clogging issues, ensuring high nitrogen oxide decomposition rates and reduced N2O emissions, enhancing catalyst durability and throughput.

JP2025010069APending Publication Date: 2025-01-20MITSUBISHI CHEM CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2024106359
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-06-30
Filing Date
2024-07-01
Publication Date
2025-01-20

AI Technical Summary

Technical Problem

Existing nitrogen oxide purification catalysts, particularly those using copper-supported zeolites, face issues with high-temperature thermal deterioration and clogging due to soot particles, leading to increased production of N2O, a potent greenhouse gas, and require higher throughput and improved durability.

Method used

A nitrogen oxide purification catalyst comprising AEI or AFX type zeolites with specific copper and manganese content, produced through a method involving a mixing, aging, and hydrothermal synthesis process in a stirred tank reactor, ensuring a SiO2/Al2O3 ratio of 5 to 12, copper content of 2% to 4.5% by weight, and manganese content of 0.5% to 3.5% by weight, with controlled copper to aluminum ratio of 0.1 to 0.3, and incorporating an organic structure directing agent.

Benefits of technology

The catalyst achieves high nitrogen oxide decomposition rates with minimal N2O generation and excellent durability at high temperatures, maintaining performance under demanding conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025010069000008
    Figure 2025010069000008
  • Figure 2025010069000009
    Figure 2025010069000009
  • Figure 2025010069000010
    Figure 2025010069000010
Patent Text Reader

Abstract

To provide a zeolite catalyst having high catalytic treating capacity per unit time, resistance to N2O generation, and excellent durability to high temperatures.SOLUTION: A nitrogen oxide purification catalyst contains an AEI zeolite or an AFX zeolite, the zeolite having a SiO2 / Al2O3 ratio (molar ratio) of 5 or more and 12 or less, contains copper and manganese as supported metals, the amount of supported copper being 2 wt.% or more and 4.5 wt.% or less, the amount of supported manganese being 0.5 wt.% or more and 3.5 wt.% or less, and an element ratio of copper to aluminum (Cu / Al) being 0.1 or more and 0.3 or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a catalyst for purifying nitrogen oxides, particularly to a catalyst for purifying nitrogen oxides contained in exhaust gas discharged from an internal combustion engine such as a diesel engine, and to a method for producing said catalyst. [Background technology]

[0002] The decomposition of nitrogen oxides in exhaust gases involves breaking down NOx into nitrogen and oxygen, and the ammonia produced by thermal decomposition of urea serves as a reducing agent. This is used in buses, trucks, and passenger cars under the name AdBlue (trademark).

[0003] Conventionally, harmful substances in exhaust gases were NO, NOx, and NOx, which are the causes of photochemical smog. 2 It means nitrous oxide (N 2 O) has not received much attention. However, N 2 O is an ozone-depleting substance, and CO 2 Since NOx is a gas with a greenhouse effect 300 times greater than that of NOx, it may be subject to stricter regulations in the future as an environmental pollutant. 2 Low O emissions are also important.

[0004] Copper-supported zeolite and iron-supported zeolite are known as catalysts for exhaust gas treatment. In particular, exhaust gas treatment catalysts using copper-supported zeolite, especially CHA-type zeolite, have very high NOx removal capabilities. However, on the other hand, they have relatively low N 2 The problem is that O is easily produced as a by-product. When exposed to high temperatures, particularly at 500°C or higher during combustion treatment, which is carried out when the filter is about to become clogged with fine soot particles produced by incomplete combustion, thermal degradation occurs easily, and improvements were needed.

[0005] In response to the above problems, for example, Patent Document 1 discloses a catalyst composition for treating exhaust gas containing a molecular sieve, and the molecular sieve is characterized by containing exchanged copper and exchanged manganese. Furthermore, Non-Patent Document 1 discloses an AEI type zeolite with an increased Cu concentration in order to obtain a high purification capacity at high temperatures. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] Special Publication No. 2021-533980 [Non-patent literature]

[0007] [Non-Patent Document 1] Zeolite, vol.36, No.2, 38-47 Summary of the Invention [Problem to be solved by the invention]

[0008] The above-mentioned Patent Document 1 describes a catalyst for selective catalytic reduction (SCR) of NOx, which improves the NOx conversion rate and reduces N 2 The production of O is reduced. Specifically, in Patent Document 1, the flow rate (SV) of the reaction gas per unit catalyst volume is 90,000 (h -1 ) 82% of 500 ppm NO is treated (see Patent Document 1, Table 1). From this, the NO treatment amount per mL of catalyst is about 45 mL / h, but catalysts with higher treatment capacity are required. In addition, the Cu / AEI zeolite disclosed in Non-Patent Document 1 has a high purification capacity at high temperatures, but 2 The problem of high O generation has not been resolved.

[0009] Therefore, the object of the present invention is to develop a catalyst with high processing capacity per unit time and N 2The present invention aims to provide a zeolite catalyst which is less likely to generate O and has excellent durability against high temperatures. [Means for solving the problem]

[0010] As a result of intensive research into the above-mentioned problems, the present inventors have found that the above-mentioned problems can be solved by using an AEI zeolite or AFX zeolite catalyst having specific amounts of copper and manganese and specific physical properties. The present invention was completed based on this finding.

[0011] That is, the gist of the present invention is as follows. [1] A catalyst for purifying nitrogen oxides containing AEI type zeolite or AFX type zeolite, 2 / Al 2 O 3 A catalyst for purifying nitrogen oxides, comprising copper and manganese as supported metals, the amount of supported copper being 2% by weight or more and 4.5% by weight or less, the amount of supported manganese being 0.5% by weight or more and 3.5% by weight or less, and the elemental ratio of copper to aluminum (Cu / Al) being 0.1 or more and 0.3 or less. [2] A method for producing a raw gel by mixing at least a Si element source, an Al element source, an alkali metal element source, and water, a maturation step of maturating the raw gel after the mixing step, a hydrothermal synthesis step, and a supporting step, the mixing step, the maturation step, and the hydrothermal synthesis step being carried out in a stirred tank reactor, and in the supporting step, copper and manganese are added to the AEI or AFX zeolite produced in the previous step, and the ratio of the Si element source to the Al element source in the raw gel is a molar ratio of the oxide of the Si element source to the oxide of the Al element source (SiO 2 / Al 2 O 3 The molar ratio of the Si element source to the alkali metal element source contained in the raw gel is 5 to 1000, and the ratio of M to the oxide of Si element is 5 to 1000. 2 O (M represents an alkali metal element source) molar ratio (M 2 O / SiO 2a molar ratio of potassium to the total alkali metal elements in the raw gel is 0 or more and 0.5 or less, and a molar ratio of potassium to the total alkali metal elements in the raw gel is 0 or more and 0.5 or less. [3] The raw gel further contains an alkaline earth metal element source, and the ratio of the Si element to the alkali metal element source and the alkaline earth metal element source contained in the raw gel is M' to the oxide of the Si element. (2 / n) The molar ratio (M') of O (M' represents an alkali metal element source or an alkaline earth metal element source, and n is calculated as 1 for an alkali metal element source and 2 for an alkaline earth metal element source) (2 / n) O / SiO 2 The method for producing a nitrogen oxide purifying catalyst according to the above [2], wherein the molar ratio of the nitrogen oxide to the nitrogen oxide is from 0.02 to 0.5. [4] A method for producing a nitrogen oxide purification catalyst according to the above [2] or [3], wherein the raw gel does not contain FAU-type zeolite but contains an organic structure-directing agent, and the ratio (molar ratio) of the organic structure-directing agent to Si atoms in the raw gel is 0.01 or more and 1 or less. Effect of the Invention

[0012] According to the present invention, the catalyst has a high processing capacity per unit time, and N 2 It is possible to provide a zeolite catalyst which is less likely to generate O and has excellent durability against high temperatures. [Brief description of the drawings]

[0013] [Figure 1] 1 is an XRD chart of powder 1 (AEI zeolite) obtained in Example 1. [Diagram 2] 1 is an XRD chart of powder 2 (AEI zeolite) obtained in Example 2. [Diagram 3] 1 is an XRD chart of powder 3 (AEI zeolite) obtained in Example 3. [Figure 4] 1 is an XRD chart of powder 4 (AEI zeolite) obtained in Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] Hereinafter, the embodiments of the present invention will be described in detail, but the following description is an example of the embodiment of the present invention, and the present invention is not limited to these contents. In addition, the embodiments of the present invention can be appropriately combined. In this specification, "to" means a range including the numerical values ​​described before and after it.

[0015] [Nitrogen oxide purification catalyst] The nitrogen oxide purification catalyst of the present invention contains AEI type zeolite or AFX type zeolite. AEI zeolite and AFX zeolite are codes that specify the zeolite framework structure defined by the International Zeolite Association (IZA), and indicate AEI and AFX structures, respectively. The structures are characterized by X-ray diffraction data. However, when measuring an actual manufactured zeolite, the intensity ratio and peak position of each peak may vary slightly due to the influence of the crystal face growth direction of the zeolite, the ratio of constituent elements, adsorbed substances, and the presence of defects, so the values ​​obtained may not be exactly the same as the parameters of the AEI and AFX structures specified by the IZA, and a margin of about 10% is allowed.

[0016] Major peaks observed in X-ray diffraction of AEI zeolite include, for example, the 110 plane peak at 2θ=9.5°±0.2°, the 022 plane peak at 16.9°±0.2°, and the 310 plane peak at 20.6°±0.2° when CuKα radiation is used as the radiation source. The main peaks observed in X-ray diffraction of AFX zeolite when CuKα radiation is used as the radiation source include the 101 plane peak at 2θ=8.6°±0.2°, the 102 plane peak at 2θ=11.6°±0.2°, and the 110 plane peak at 12.9°±0.2°.

[0017] The SiO of the AEI zeolite or AFX zeolite in the present invention 2 / Al 2 O3 The ratio (molar ratio) must be between 5 and 12. In the SCR reaction, the aluminum sites in the zeolite pores have two functions. One is to act as an ion exchange site that holds copper ions, which become catalytically active sites, and the other is to act as an ammonia adsorption site that acts as a NOx reducing agent. SiO 2 / Al 2 O 3 When the molar ratio is 12 or less, the amount of copper ions and the amount of ammonia adsorbed are sufficient, and the conversion rate of the decomposition activity of NOx is maintained without decreasing. 2 / Al 2 O 3 A molar ratio of 5 or more is preferable because dealumination is unlikely to occur even when exposed to high-temperature steam. In other words, dealumination does not reduce the solid acid sites, so the ammonia adsorption capacity does not decrease and NOx purification performance is maintained. In addition, the copper ions in the zeolite pores are stably held and do not become liberated. The liberated copper aggregates on the outer surface of the zeolite pores to form copper oxide fine particles. Unlike the copper sites in the zeolite pores, these copper oxide fine particles have low NOx decomposition activity, and therefore the NOx purification performance decreases accordingly. In contrast, SiO 2 / Al 2 O 3 When the ratio (molar ratio) is 5 or more, no copper ions are liberated, and high NOx decomposition activity is maintained. In addition, copper oxide is produced by the combustion of ammonia, 2 As a result, N 2 This can cause an increase in O emissions, but this problem does not occur. From the above perspective, SiO 2 / Al 2 O 3 The ratio (molar ratio) is more preferably 7 or more and 11.5 or less, and particularly preferably 8 or more and 11 or less.

[0018] The Si and Al contents of the zeolite of the present invention can usually be measured by ICP elemental analysis or X-ray fluorescence analysis. In X-ray fluorescence analysis, a calibration curve of the fluorescent X-ray intensity of the analyzed element in a standard sample and the atomic concentration of the analyzed element is created, and the silicon atom and aluminum contents in the zeolite sample can be determined by X-ray fluorescence analysis (XRF) using this calibration curve.

[0019] The nitrogen oxide purification catalyst of the present invention is characterized by containing copper and manganese as supported metals. The inclusion of copper promotes the decomposition of NOx, resulting in a high conversion rate. In addition, the inclusion of manganese improves the durability of the catalyst. The amount of copper supported in the nitrogen oxide purification catalyst of the present invention is 2% by weight or more and 4.5% by weight or less. When it is 2% by weight or more, the effect of the present invention can be fully exhibited and NOx can be decomposed with a sufficient conversion rate. On the other hand, when the amount of copper supported is 4.5% by weight or less, aggregation between copper ions and the formation of copper oxide fine particles are unlikely to occur, and as a result, N 2 The effect of the present invention can be achieved by suppressing the amount of O discharged. From the above viewpoints, the amount of supported copper is preferably 2.5% by weight or more and 4.0% by weight or less. The amount of manganese supported in the nitrogen oxide purification catalyst of the present invention is 0.5% by weight or more and 3.5% by weight or less. If it is 0.5% by weight or more, the durability of the catalyst is sufficient. On the other hand, if it is 3.5% by weight or less, the excess manganese does not block the zeolite pores, and the diffusibility of the reactants into the zeolite pores is maintained. From the above points, the amount of manganese supported is preferably 1.5% by weight or more and 3.5% by weight or less.

[0020] In the nitrogen oxide purification catalyst of the present invention, the ratio of copper to aluminum elements (Cu / Al) is 0.1 or more and 0.3 or less. When Cu / Al is 0.1 or more, the amount of ammonia adsorbed decreases, but the number of copper ion sites, which are active sites, increases, and the reaction rate increases. On the other hand, when Cu / Al is 0.3 or less, the copper ion density in the pores decreases, and the activity of the catalyst decreases, but on the other hand the amount of ammonia adsorbed increases, and the adsorption of ammonia does not become the rate limiting factor, resulting in an increase in the reaction rate. Furthermore, it is believed that the ammonia in the pores acts as a copper ligand, forming an ammine complex ion at the copper ion site, thereby protecting the copper ion site from the formation of copper oxide due to reaction with oxygen molecules. However, when the amount of ammonia adsorbed decreases, the protective effect decreases, copper oxide particles are formed, and as a result, N 2 This causes an increase in the amount of O generated. From the above points, Cu / Al is preferably 0.12 or more and 0.25 or less, and more preferably 0.15 or more and 0.23 or less.

[0021] The Cu content of the nitrogen oxide purification catalyst of the present invention can be usually measured by ICP elemental analysis or X-ray fluorescence analysis. In X-ray fluorescence analysis, a calibration curve of the fluorescent X-ray intensity of an analyzed element in a standard sample and the atomic concentration of the analyzed element is prepared, and the copper atom content in the sample can be determined by X-ray fluorescence analysis (XRF) using this calibration curve.

[0022] Manganese can also be measured in the same way by ICP elemental analysis or X-ray fluorescence analysis. Since it can be difficult to completely dissolve the sample, XRF is generally used. The amount of metal (including copper or manganese) supported in the nitrogen oxide purification catalyst of the present invention can be calculated from the ratio of supported amount / catalyst weight when the weight (supported amount) of the supported metal is known. Even when the supported amount is unknown, it can be calculated from the measurement results of ICP elemental analysis or fluorescent X-ray analysis. In other words, the amount of metal (including copper or manganese) supported in the nitrogen oxide purification catalyst of the present invention is calculated from the ratio of the amount of supported metal / catalyst weight when the weight of the supported metal (amount of supported metal) is known, and when the amount of supported metal is unknown, it means a calculation based on the measurement results of ICP elemental analysis or X-ray fluorescence analysis.

[0023] In the nitrogen oxide purification catalyst of the present invention, copper and manganese may be present on the external surface of the zeolite or may be present within the pores of the zeolite. In order to enhance the dispersibility of copper and manganese and improve the catalytic activity or catalyst life, however, it is preferable for them to be present within the pores.

[0024] In the nitrogen oxide purification catalyst of the present invention, examples of methods for incorporating metals (copper and manganese) include an ion exchange method, an impregnation support method, a precipitation support method, a solid-phase ion exchange method, a CVD method, a spray drying method, and the like. Among these, the ion exchange method, the impregnation support method, and the spray drying method are preferred for supporting a metal on the AEI zeolite or AFX zeolite of the present invention.

[0025] In addition, the catalyst can be mixed with a binder, granulated, or molded into a predetermined shape such as a honeycomb. Specifically, for example, the catalyst can be mixed with an inorganic binder such as silica, alumina, or clay mineral, or with inorganic fibers such as alumina fiber or glass fiber, and then granulated or molded into a predetermined shape such as a honeycomb by an extrusion method or a compression method, and then fired to obtain a granular catalyst, honeycomb catalyst, or catalyst molded product. Furthermore, the catalyst may be applied to a substrate such as a sheet or honeycomb. Specifically, for example, the nitrogen oxide purification catalyst of the present invention is mixed with an inorganic binder such as silica, alumina, or clay mineral to prepare a slurry, which is then applied to the surface of a substrate made of an inorganic material such as cordierite, and then fired. Preferably, the catalyst is applied to a substrate having a honeycomb shape, thereby obtaining a honeycomb-shaped honeycomb catalyst coated with the catalyst.

[0026] The specific surface area of ​​the nitrogen oxide purification catalyst of the present invention is not particularly limited, but since there are many active sites on the inner surface of the pores, it is preferable that the specific surface area is 300 m 2 / g or more, 1000m 2 / g or less is preferable, and 350m 2 / g or more, 800m 2 / g or less, more preferably 450m 2 / g or more, 750m 2 The specific surface area of ​​the catalyst is measured by the BET method or the like.

[0027] The nitrogen oxide purification catalyst of the present invention can be used in various exhaust purification systems. Specifically, the nitrogen oxide purification catalyst of the present invention can purify nitrogen oxides contained in a wide variety of exhaust gases emitted from various diesel engines, boilers, gas turbines, etc. for diesel automobiles, gasoline automobiles, stationary power generation, ships, agricultural machinery, construction machinery, motorcycles, and aircraft. In addition, when using the catalyst of the present invention, the contact conditions between the catalyst and the exhaust gas are not particularly limited, but the space velocity of the exhaust gas is usually 100 (h -1 ) or more, preferably 1000(h -1 ) or more, and more preferably 5000 (h -1 ) or more, usually 500,000 (h -1 ) or less, preferably 400,000 (h -1 ) or less, more preferably 300,000 (h -1 ) or less, and the temperature is usually 100°C or more, more preferably 125°C or more, even more preferably 150°C or more, and is usually 1000°C or less, preferably 800°C or less, even more preferably 700°C or less, and particularly preferably 600°C or less.

[0028] [Method of manufacturing nitrogen oxide purification catalyst] The method for producing a nitrogen oxide purification catalyst of the present invention is characterized by using an AEI or AFX zeolite produced by a specific production method, and specifically, in the supporting step, copper and manganese are added to the AEI or AFX zeolite produced in the previous step. In this supporting step, the zeolite can be used simply in the form of a powder, but it is preferable to use the zeolite in the form of a molded body described later because it is easy to handle. The method for producing the AEI or AFX zeolite includes a mixing step of mixing a Si element source, an Al element source, an alkali metal element source, and water to obtain a raw material gel, an aging step of aging the raw material gel after the mixing step, and a hydrothermal synthesis step. It is also characterized in that these steps are carried out in a stirred tank reactor. And, in order to make the raw material gel into a nitrogen oxide purification catalyst, it includes a supporting step of adding copper and manganese. Each step will now be described in detail.

[0029] Hereinafter, the raw materials used in the production method of the present invention will be described in more detail. <Si element source> The Si element source is a compound having Si atoms (hereinafter, may be referred to as "Si compound" or "Si element raw material"). In the hydrothermal synthesis step, an amorphous Si compound that is considered to be easily soluble is preferable so that the Si / Al ratio suitable for the crystallization of zeolite is obtained. As the amorphous Si compound, colloidal silica, amorphous silica, fumed silica, amorphous silicas such as sodium silicate, and silane oligomers, silica sols, and gel-like Si compounds formed by their aggregation (hereinafter, may be referred to as "silane polymers") obtained by hydrolyzing and polymerizing alkoxysilanes such as tetraethyl orthosilicate; aluminosilicate gels and the like can be used. These may be used alone or in combination of two or more in any ratio. Among these, amorphous Si compounds are preferable because they are easily soluble and inexpensive. Further, from the viewpoints of being easily mixed uniformly with other raw materials and being easily soluble in water, colloidal silica, silane polymers, and aluminosilicate gels are preferable. As the Si element raw material, among those described above, colloidal silica is particularly preferable. In the production method of the present invention, it is preferable not to use FAU-type zeolite or the like that has been conventionally used as the Si element source or the Al element source described later. The reasons include poor productivity and the fact that it is not necessary to use it in the present invention. Therefore, even if FAU-type zeolite or the like is used, it is preferably 1% by weight or less in the Si element source, and it is more preferable not to use it.

[0030] <Al element source> The Al element source is a compound containing Al atoms (hereinafter, may be referred to as "Al compound" or "Al element raw material"). The Al compound is preferably a compound that is easily soluble in water. In addition, it is preferably a compound that is well mixed with the Si compound and is easily soluble so that the Si / Al ratio is suitable for the crystallization of zeolite in the aging and hydrothermal synthesis steps. From the above viewpoints, the Al compound is preferably amorphous aluminum hydroxide, aluminum hydroxide having a gibbsite structure, aluminum hydroxide having a bayerite structure, aluminum nitrate, aluminum sulfate, aluminum oxide, sodium aluminate, boehmite, pseudo-boehmite, aluminum alkoxide, etc. These may be used alone or in any ratio and combination of two or more. Among these, particularly preferred are amorphous aluminum hydroxide, aluminum hydroxide having a gibbsite structure, and aluminum hydroxide having a bayerite structure. As the Al compound, it is preferable to use a non-crystalline aluminum atom raw material, and among the above, amorphous aluminum hydroxide is particularly preferred.

[0031] (Amount of Al element source added) The Al element source is a source of Si and Al in the raw gel, and the molar ratio of the oxide of the Si element source to the oxide of the Al element source (SiO 2 / Al 2 O 3 The molar ratio of the aryl group to the alkyl group must be 5 or more and 1,000 or less. SiO 2 / Al 2 O 3 By setting the molar ratio within the above range, the target zeolite can be easily obtained. From the above perspective, SiO 2 / Al 2 O 3 The molar ratio is more preferably 8 or more and 500 or less, further preferably 10 or more and 100 or less, and particularly preferably 12 or more and 50 or less.

[0032] <Alkaline metal element source> The alkali metal element source is not particularly limited, and may be a compound containing an alkali metal atom, and preferably, an alkali metal ion is contained in the aqueous reactant precursor before hydrothermal synthesis. As the alkali metal element source, inorganic acid salts such as hydroxides, oxides, sulfates, nitrates, phosphates, chlorides, bromides, and organic acid salts such as acetates, oxalates, and citrates of the above-mentioned alkali metal atoms can be used. The alkali metal element source may be used alone or in any combination of two or more kinds in any ratio. As the alkali metal element, known alkali metal elements used in the synthesis of zeolites can be used. Specifically, at least one selected from lithium, sodium, potassium, rubidium, and cesium is preferable. By including these alkali metal elements, the crystallization of zeolites can be easily promoted, and the amount of expensive OSDA added can be reduced. Among the above alkali metal elements, sodium and potassium are particularly preferred, and it is preferable that the sodium atom content is 25 mol % or more. The alkali metal elements may be used alone or in combination of two or more. In addition, when several kinds of alkali metal elements are mixed, a mixture of sodium element and potassium element is preferable. In the present invention, it is particularly preferable that the alkali metal element contains at least potassium element. In addition, the molar ratio of potassium to the total alkali metal elements in the raw gel is 0 to 0.5, and preferably 0.1 to 0.5. By setting the content (molar ratio) of potassium in the alkali metal elements to the above range, it is possible to reduce the viscosity of the raw gel, and a uniform raw gel can be prepared in a short time in the mixing process. In addition, even if potassium is blended within the above range, it does not affect the structure and physical properties of the produced zeolite. For the above reasons, the more preferable content of potassium is more preferably 0.15 to 0.4, and more preferably 0.2 to 0.3, in terms of the molar ratio of potassium to the total alkali metal source.

[0033] (mixed amount of alkali metal elements) The ratio of Si element to alkali metal element contained in the raw gel is M (2 / n) O (M is an alkali metal element, and n is 1) molar ratio (M (2 / n) O / SiO 2 The molar ratio of the oxide of the alkali metal element to the oxide of the Si element (M (2 / n) O / SiO 2 The molar ratio of the alkali metal element to the Al atom contained in the aqueous reactant precursor is more preferably in the range of 0.02 to 0.5. The molar ratio of the alkali metal element to the Al atom contained in the aqueous reactant precursor is preferably in the range of 0.8 to 1.2.

[0034] <Source of alkaline earth metal elements> In the manufacturing method of the present invention, in addition to the alkali metal, an alkaline earth metal element may be further mixed in. Examples of the alkaline earth metal include beryllium, magnesium, calcium, strontium, and barium. As the raw material of the alkaline earth metal element, inorganic acid salts such as hydroxides, oxides, sulfates, nitrates, phosphates, chlorides, bromides, etc., and organic acid salts such as acetates, oxalates, citrates, etc., of the above-mentioned alkaline earth metal atoms can be used. The alkaline earth metal element raw materials may be used alone or in any combination of two or more kinds in any ratio.

[0035] (Mixing amount of alkali metal element source and alkaline earth metal element source) The ratio of the Si element source to the alkali metal element source and the alkaline earth metal element source contained in the raw material gel is M (2 / n) Molar ratio of O (M (2 / n) O / SiO 2 The molar ratio is preferably 0.02 to 0.5, inclusive, where M represents an alkali metal element or an alkaline earth metal element, and n is 1 for an alkali metal and 2 for an alkaline earth metal. That is, the total amount of the alkali metal source and the alkaline earth metal source (hereinafter sometimes referred to as "alkali") is preferably 0.02 or more and 0.5 or less in terms of the molar ratio to the oxide of the Si element source. When the amount of alkali is within the above range, the target zeolite is easily obtained. From the above viewpoint, the amount of alkali is more preferably in the range of 0.05 to 0.4.

[0036] <Organic Structure Directing Agents (OSDA)> In the present invention, it is preferable that the raw gel contains an organic structure directing agent. The content of the organic structure directing agent is preferably 0.01 or more and 1 or less in molar ratio to the Si atoms contained in the raw gel. In addition, since OSDA is expensive among the synthesis raw materials, it is preferable to reduce the amount used. On the other hand, from the viewpoint of obtaining a high purity target zeolite, it is preferable to contain a certain amount or more of OSDA. From the above viewpoint, that is, from the viewpoint of being able to obtain a high purity target zeolite while being inexpensive, the content of OSDA is more preferably 0.02 or more in molar ratio to the Si atoms, even more preferably 0.05 or more, and more preferably 0.5 or less, even more preferably 0.3 or less, and particularly preferably 0.15 or less. Furthermore, when preparing the Si element source, Al element source, alkali metal element source, and water (hereinafter sometimes referred to as "mixed raw materials") for obtaining the raw material gel, OSDA does not need to be added, and may be added in portions or all at once. There are no particular limitations on the timing of OSDA addition, and it may be added when obtaining the raw material gel, before aging, or immediately before hydrothermal synthesis. When obtaining the raw material gel, it is preferable that OSDA is contained in a liquid obtained by mixing water and an alkali metal element source (hereinafter sometimes referred to as an alkaline solution). As the OSDA, nitrogen-containing organic structure-directing agents such as quaternary ammonium cations, phosphorus-containing organic structure-directing agents, etc. can be used. Among these, nitrogen-containing organic structure-directing agents are preferred because they are less likely to generate harmful substances during firing.

[0037] For example, examples of nitrogen-containing organic structure-directing agents for producing AEI zeolite include N,N-diethyl-2,6-dimethylpiperidinium cation, N,N-dimethyl-9-azoniabicyclo[3.3.1]nonane cation, N,N-dimethyl-2,6-dimethylpiperidinium cation, N-ethyl-N-methyl-2,6-dimethylpiperidinium cation, N,N-diethyl-2-ethylpiperidinium cation, N,N-dimethyl-2-(2-hydroxyethyl)piperidinium cation, N,N-dimethyl-2-ethylpiperidinium cation, N,N-dimethyl-3,5-dimethylpiperidinium cation, N-ethyl-N-methyl-2-ethylpiperidinium cation, 2,6-dimethyl-1-azonium[5.4]decane cation, and N-ethyl-N-propyl-2,6-dimethylpiperidinium cation. Of these, N,N-dimethyl-3,5-dimethylpiperidinium cation is preferred, and N,N-dimethyl-3,5-dimethylpiperidinium hydroxide is more preferred. In addition, as a phosphorus-containing organic structure directing agent for producing AEI type zeolite, a substance such as tetrabutylphosphonium or diphenyldimethylphosphonium can be used.

[0038] For example, examples of nitrogen-containing organic structure-directing agents for producing AFX zeolite include 1,4-bis(1,4-diazabicyclo[2.2.2]octane)butanediammonium cation, N,N,N',N'-tetraethylbicyclo[2.2.2]oct-7-ene-2,3:5,6-dipyrrolidinium cation, 1,3-di(1-adamantyl)imidazolium cation, and N,N,N,N',N',N'-hexaethylpentanediammonium cation. Among these, 1,4-bis(1,4-diazabicyclo[2.2.2]octane)butanediammonium cation and N,N,N,N',N',N'-hexaethylpentanediammonium cation are preferred, and among these, 1,4-bis(1,4-diazabicyclo[2.2.2]octane)butanediammonium dihydroxide and N,N,N,N',N',N'-hexaethylpentanediammonium dibromide are more preferred.

[0039] These OSDAs may be used alone or in any combination of two or more kinds in any ratio.

[0040] (Amount of water added) The raw gel according to the present invention contains water (H 2 The amount of water added is usually 5 or more, preferably 7 or more, in terms of a molar ratio to the silicon atoms contained in the gel mixture before hydrothermal synthesis, from the viewpoint of mitigating the unevenness of heat and raw materials in the reactor and creating an environment in which zeolite is easily crystallized. From the viewpoint of reducing the amount of waste liquid to be treated, improving the one-batch efficiency (amount of zeolite recovered in one vessel during hydrothermal synthesis), and enabling low-cost production by shortening the synthesis time, the amount of water to be added is usually 50 or less, preferably 40 or less, more preferably 30 or less, further preferably 25 or less, and particularly preferably 20 or less, in terms of the molar ratio to the Si atoms contained in the raw material before hydrothermal synthesis. Water may be added in portions or all at once.

[0041] <Seed crystal> In the production method of the present invention, it is preferable to have seed crystals in the raw material gel. Zeolite is preferable as the type of seed crystal, and the zeolite added as seed crystals in the present production method preferably has a framework density of 14T / 1000Å or more and 19T / 1000Å or less (hereinafter, this zeolite may be referred to as "zeolite added in the present invention"). Here, the framework density is a value described in ATLAS of zeolite framework types Sixth revised Edition, 2007, ELSEVIER by CH. Baerlocher et al., and is a value that represents the framework density. In other words, the framework density is the value calculated based on the unit volume of zeolite (1000Å). 3 This refers to the number of T atoms (atoms other than oxygen atoms that make up the zeolite framework structure) present per unit area, and this value is determined by the structure of the zeolite. It is also desirable that the seed crystals to be added have a common CBU (composite building unit) with the target zeolite. 4 The zeolite seed crystals are formed by linking units and are the structural units of zeolite. The zeolite seed crystals added in the present invention may be one type of zeolite alone or two or more types in any ratio and combination. The seed crystals may be uncalcined products that have not been calcined after hydrothermal synthesis, calcined products that have been calcined after hydrothermal synthesis, or ion-exchanged products. 2 In cases where the fired product is easily dissolved due to conditions such as the amount of oxygen (O) and the synthesis environment (temperature, pH of the slurry), it is preferable to use an unfired product.

[0042] The amount of seed crystals added is determined so that all the Si atoms in the gel before the hydrothermal synthesis are SiO 2 In this case, SiO 2The content is preferably 1% by mass or more, and in order to promote crystallization, it is preferably 2% by mass or more, particularly preferably 3% by mass or more, and most preferably 5% by mass or more. Since the seed crystals are synthesized zeolite, it is preferably 20% by mass or less, particularly preferably 10% by mass or less, from the viewpoint of production efficiency.

[0043] <Mixing process> The mixing step in the present invention is a step of obtaining a raw gel by mixing a Si element source, an Al element source, an alkali metal element source, and water as essential ingredients. More specifically, the raw gel of the target zeolite according to the present invention is obtained by mixing an alkali metal element source, a Si element source, an Al element source, and water. Here, an alkaline earth metal element source may be added together with the alkali metal element source, and seed crystals and an organic structure directing agent (OSDA; hereinafter, sometimes referred to as "OSDA") may also be added. The production method of the present invention is a production method which includes a step of subjecting the raw material gel to aging and hydrothermal synthesis in a stirred tank reactor, and produces the target zeolite.

[0044] When preparing the raw material gel, the order of addition of each raw material is not particularly limited, but from the viewpoint of easy control of viscosity change during mixing, it is preferable to add an aqueous solution (the above-mentioned alkaline solution) in which an alkali metal element source and an alkaline earth metal element source, which is added as necessary, are dissolved, and an organic structure-directing agent, if necessary, to the Si element source and Al element source. The organic structure-directing agent may be contained in the raw materials for synthesizing the raw material gel from the beginning, or may be added after the aging process described below and immediately before the hydrothermal synthesis.

[0045] (Mixed condition) Although there are no particular limitations on the mixing conditions for obtaining the raw gel described above, from the viewpoint of facilitating the preparation of a uniform raw gel, the average peripheral speed of the stirring system is desirably 2 m / s or more, more desirably 7 m / s or more, and particularly desirably 10 m / s or more. On the other hand, from the viewpoint of reducing the load on the drive unit in terms of system design and suppressing liquid splashing, it is desirably 30 m / s or less, more desirably 27 m / s or less, and particularly desirably 25 m / s or less.

[0046] (mixing time) The mixing time is not particularly limited, but from the viewpoint of purity and uniformity, a long mixing time is preferable. On the other hand, from the viewpoint of production efficiency, a short mixing time is preferable. Therefore, the mixing time is preferably 30 seconds or more, and particularly preferably 60 seconds or more. On the other hand, it is preferably 7200 seconds or less, more preferably 1800 seconds or less, and particularly preferably 600 seconds or less.

[0047] The peripheral speed can be calculated by the following procedure. Circumferential speed (m / s) = π × diameter of mixing blade (m) × rotation speed ( / min) × 1 / 60 (min / s) The peripheral speed does not necessarily have to be constant, and may change continuously. In such a case, when a constant mixing time a is given under a certain peripheral speed A, and then mixing is performed for a constant mixing time b under a peripheral speed B, the peripheral speed calculated by the following formula is defined as the average peripheral speed. In other words, the average peripheral speed is the product of the peripheral speed and the mixing time at each peripheral speed divided by the total mixing time. Average peripheral speed (m / s) = (peripheral speed A × a + peripheral speed B × b + ··· + peripheral speed N × n) / total mixing time (a + b + ··· + n) In the present invention, since stirring may be continued in the subsequent maturation step to prevent settling and to achieve more uniform mixing, the time during which stirring is continued in a state containing a Si element source, an Al element source, an alkali metal element source, and water at the aforementioned preferred peripheral speed, for example, a peripheral speed of 2 m or more, within the aforementioned preferred mixing time range may be regarded as the mixing step.

[0048] <Aging process> In the production method of the present invention, the raw gel obtained as described above is aged. (Aging conditions) The aging temperature is not particularly specified, but in order to avoid poorly soluble crystal precursors, the raw material gel is aged at a temperature of preferably 140° C. or less, more preferably 120° C. or less, and particularly preferably 100° C. or less. On the other hand, the temperature is preferably 30° C. or more, more preferably 40° C. or more, and particularly preferably 50° C. or more. The temperature may be constant during aging, or may be changed stepwise or continuously.

[0049] (Aging time) The maturation time is not particularly limited. From the viewpoint of production efficiency, a short time is preferable, but from the viewpoint of purity and uniformity, it is preferable to carry out the maturation for a long time. Specifically, the maturation time is preferably 15 minutes or more, more preferably 30 minutes or more, and particularly preferably 60 minutes or more. On the other hand, it is preferably 36 hours or less, more preferably 24 hours or less, and particularly preferably 12 hours or less. The maturation is preferably carried out without applying external pressure because the apparatus required is simple. In addition, the maturation is preferably performed with stirring, since the raw materials are easily homogenized. The stirring method is not particularly limited. During maturation, a part or all of the remaining raw materials (e.g., seed crystals and ODSA) that have not yet been added may be added.

[0050] <Hydrothermal synthesis> In this production method, after aging, any remaining raw materials (e.g., seed crystals or ODSA) that have not yet been added are added so as to obtain a predetermined raw material composition, and hydrothermal synthesis is performed. The target zeolite is synthesized by hydrothermal synthesis. Hydrothermal synthesis is usually performed by placing the composition after the addition of zeolite in a pressure-resistant container and maintaining a predetermined temperature under self-generated pressure, while stirring, while rotating or rocking the container, or in a stationary state. Hydrothermal synthesis is usually performed at 140°C or higher. In addition, hydrothermal synthesis is usually performed at 220°C or lower, preferably 200°C or lower, and more preferably 190°C or lower. The reaction time is not particularly limited, but is usually 2 hours or more, preferably 3 hours or more, more preferably 5 hours or more, and particularly preferably 12 hours or more, while it is usually 14 days or less, preferably 7 days or less, more preferably 5 days or less, and even more preferably 2 days or less. The reaction temperature may be constant during the reaction, or may be changed stepwise or continuously. The stirring speed may be constant during the reaction, or may be changed stepwise or continuously. By carrying out the hydrothermal synthesis under the above conditions, the yield of the target zeolite is improved, impurities are less likely to be produced, and the production costs can be reduced, which is preferable.

[0051] (Zeolite Recovery) After hydrothermal synthesis, the zeolite is separated from the composition after hydrothermal synthesis (hydrothermal synthesis reaction liquid). The obtained zeolite usually contains alkali metal atoms in the pores. Furthermore, when an organic structure-directing agent is used, the zeolite usually contains the organic structure-directing agent in the pores. Hereinafter, the substances contained in the pores of the zeolite after hydrothermal synthesis, such as the organic structure-directing agent or alkali metal, may be referred to as "structure-directing agent, etc.", and the zeolite containing this in the pores may be referred to as "SDA, etc.-containing zeolite." The method for separating the SDA-containing zeolite from the hydrothermal synthesis reaction liquid is not particularly limited, but typically includes filtration, decantation, direct drying, and the like.

[0052] The SDA-containing zeolite separated and recovered from the hydrothermal synthesis reaction liquid is washed with water, dried, and then calcined or otherwise treated to remove the structure-directing agent, etc., used during the production.

[0053] The method for removing the structure-directing agent from the zeolite containing SDA or the like may be a liquid phase treatment using an acidic solution or a chemical solution containing a structure-directing agent decomposing component, an ion exchange treatment using a resin or the like, or a thermal decomposition treatment, or a combination of these treatments. The organic structure-directing agent contained therein can be removed by a method such as extraction with an organic solvent such as an aqueous ethanol solution. On the other hand, from the viewpoint of productivity, removal of the organic structure directing agent and the like by calcination is preferred. Usually, calcination is performed in air or an oxygen-containing inert gas, or in an inert gas atmosphere at a temperature of 300 to 1000°C. The calcination temperature is preferably 400°C or higher, more preferably 450°C or higher, and even more preferably 500°C or higher, and is preferably 900°C or lower, more preferably 800°C or lower, and even more preferably 700°C or lower. Nitrogen or the like can be used as the inert gas.

[0054] By the above-mentioned production method of the present invention, AEI zeolite or AFX zeolite is synthesized.

[0055] (AEI type zeolite) The AEI zeolite produced by the production method of the present invention is suitable as the zeolite to be used in the nitrogen oxide purification catalyst of the present invention.

[0056] According to the production method of the present invention, it is possible to obtain high-purity AEI zeolite on a large scale while reducing the amount of expensive organic structure-directing agent used.

[0057] As the purity of the target AEI zeolite increases, the performance such as catalytic activity when used as a catalyst improves. Therefore, the purity of the target AEI zeolite is preferably 80% or more, more preferably 85% or more, and particularly preferably 90% or more. The higher the purity of the target zeolite, the better, and the upper limit is 100%.

[0058] The purity of AEI zeolite can be calculated by the following procedure. First, the by-product content in the zeolite is calculated. The by-product content can be calculated from the following formula (1) using an XRD chart obtained by XRD measurement using CuKα radiation as a radiation source. By-product content (%) = I (peak intensity of by-product) / I (peak intensity of AEI zeolite + by-product) × 100 (1)

[0059] In the above formula (1), I(AEI) is the intensity of the main peak of AEI. The main peak is the most intense peak among the XRD peaks that characterize each zeolite, and in the case of AEI zeolite, it is typically the peak at 2θ=9.5°±0.2°. I(by-product) is the intensity of the main peak of the by-product. I(by-product) is the intensity of the XRD peak that characterizes the structure of the by-product. For example, when the by-product zeolite is a MOR type zeolite, I(by-product) is the intensity of the XRD peak having a peak top at 2θ=6.5±0.1°. When the by-product zeolite is a GME type zeolite, I(by-product) is the intensity of the XRD peak having a peak top at 2θ=7.5±0.1°. When the by-product zeolite is a MER type zeolite, I(by-product) is the intensity of the XRD peak having a peak top at 2θ=12.5±0.1°. When the by-product zeolite is an ANA type zeolite, I(by-product) is the intensity of the XRD peak having a peak top at 2θ=15.9±0.1°. When the by-product is sanidine, I(by-product) is the intensity of the XRD peak having a peak top at 2θ=21.7±0.1°. When there are two or more types of by-products, I (by-products) is calculated by adding up the peak intensities.

[0060] From the by-product content (%) calculated as above, the purity of the AEI zeolite can be calculated from the following formula (2). Purity of AEI zeolite (%) = 100 - by-product content (%) (2) Since the same determination can be made for the AFX type, the explanation is given here for the AEI type, but the preferred ranges of purity, etc. are the same as for the AEI type. In both the AEI and AFX types, the openings between the cages in the zeolite are narrow, so the movement (diffusion) of Cu ions between the cages is moderately suppressed, which suppresses the aggregation of Cu. As a result, there is no deterioration in NOx purification performance due to heat or water vapor, and no N 2 Since an increase in O emission is suppressed, it can be suitably used in the present invention.

[0061] <Supporting step of adding copper and manganese> (Metal Loading Method) When producing the catalyst of the present invention, a supporting step is carried out in which copper and manganese are added to the AEI or AFX zeolite obtained by the above-mentioned production method. At this time, other metals may be added in addition to copper and manganese. The method of adding copper, manganese, etc. to this zeolite (hereinafter sometimes referred to as a metal species supporting method) is not particularly limited, but commonly used ion exchange method, impregnation supporting method, precipitation supporting method, solid phase ion exchange method, CVD method, etc. are used. The ion exchange method and impregnation supporting method are preferred. Copper and manganese may be supported simultaneously, or may be supported one by one in sequence. The metal source of the metal species is not particularly limited, but typically a metal salt such as a nitrate, sulfate, acetate, or hydrochloride can be used. When impregnation is performed, the dispersion medium is removed from the slurry state and then dried. As a method for removing the dispersion medium, methods such as reduced pressure filtration, pressure filtration, and centrifugal filtration are preferred, and the drying temperature after filtration is preferably 50°C or higher and 200°C or lower, more preferably 70°C or higher and 150°C or lower. There are no particular limitations on the atmosphere during drying, but an inert atmosphere such as air, nitrogen, or argon is preferred. In addition, spray drying is also preferred because it allows the dispersion medium to be removed and the drying to be performed in a short time.

[0062] After drying, heat treatment is usually performed at 400° C. to 900° C. Heat treatment is preferably performed at 450° C. or higher to enhance the dispersion of metals and their interaction with the zeolite surface. The atmosphere for the heat treatment is not particularly limited, and the heat treatment is performed in an inert atmosphere such as air, nitrogen, or argon, which may contain water vapor. The heat treatment referred to here includes treatments such as steam treatment carried out when measuring the physical properties of the nitrogen oxide purification catalyst of the present invention as described above, and treatments including calcination, which will be described later, carried out when producing the nitrogen oxide purification catalyst of the present invention. The method of heat treatment is not particularly limited, and a muffle furnace, a kiln, a fluidized calcination furnace, etc. can be used, but a method of calcining by passing the above-mentioned gas is preferable. The flow rate of the gas is not particularly limited, but the flow rate of the gas per 1 g of powder is usually 0.1 ml / min or more, preferably 5 ml / min or more, and usually 100 ml / min or less, preferably 20 ml / min or less, and the catalyst obtained by the present invention is obtained by heat treatment under a gas flow.

[0063] By setting the amount of gas flowing per gram of powder to be equal to or more than the lower limit, any acid remaining in the dry powder is reliably removed during heating, reducing the possibility of the zeolite being damaged, whereas by setting the amount of gas flowing per gram of powder to be equal to or less than the upper limit, scattering of the powder can be prevented. The temperature for the heat treatment in the present invention is not particularly limited, but the treatment can be carried out usually at 250° C. or higher, preferably at 500° C. or higher, and usually at 1000° C. or lower, preferably at 900° C. or lower. By setting the temperature at or above the lower limit, the metal source can be decomposed reliably, and by setting the temperature at or below the upper limit, the structure of the zeolite is unlikely to be destroyed.

[0064] <Method of manufacturing nitrogen oxide purification catalyst> In the method for producing a nitrogen oxide purification catalyst of the present invention, as described above, a mixture of a zeolite, a metal source containing desired metals including at least copper and manganese, and a dispersion medium is prepared, and the mixture is calcined after removing the dispersion medium. The production method of the present invention will be described in detail below.

[0065] <Mixture of zeolite, metal source and dispersion medium> First, a mixture of AEI or AFX type zeolite (hereinafter sometimes simply referred to as zeolite), a metal source, and a dispersion medium (hereinafter sometimes simply referred to as mixture) is prepared.

[0066] The dispersion medium in the present invention refers to a liquid for dispersing zeolite. The mixture used in the present invention is usually in the form of a slurry or cake, with the slurry being preferred from the viewpoint of operational applicability. The type of dispersion medium used in the present invention is not particularly limited, but typically water, alcohol, ketone, etc. are used, and from the viewpoint of safety during heating, it is preferable to use water as the dispersion medium.

[0067] The order of mixing the mixture used in the present invention is not particularly limited, but usually, first, the metal source is dissolved or dispersed in the dispersion medium, and then the zeolite is mixed therewith. The solid content in the slurry prepared by mixing the above components is usually 5% by mass or more and 60% by mass or less, preferably 10% by mass or more and 50% by mass or less. By making the solid content ratio equal to or more than the lower limit, the amount of dispersion medium to be removed is large, and the time and energy of the dispersion medium removal step can be saved. In addition, by making the solid content ratio equal to or less than the upper limit, the metal tends to be more uniformly dispersed on the zeolite.

[0068] The temperature for preparing the mixture used in the present invention is usually 0° C. or higher, preferably 10° C. or higher, and usually 80° C. or lower, preferably 60° C. or lower. Zeolite usually generates heat when mixed with a dispersion medium, and by setting the mixing temperature to the above upper limit or lower, the possibility of the zeolite itself being decomposed by an acid or alkali can be reduced. The lower limit of the mixing temperature is the melting point of the dispersion medium.

[0069] The pH of the mixture used in the present invention during preparation is not particularly limited, but is usually at least 3, preferably at least 4, and more preferably at least 5, and is usually at most 10, preferably at most 9, and more preferably at most 8. By adjusting the pH to be at least the lower limit and at most the upper limit, the possibility of the zeolite being destroyed is reduced. Various additives may be added to the mixture used in the present invention to adjust the viscosity of the mixture or to control the particle shape and particle size after removal of the dispersion medium. The type of additive is not particularly limited, but inorganic additives are preferred, such as inorganic sols and clay-based additives. As inorganic sols, silica sols, alumina sols, titania sols, etc. are used, with silica sols being preferred. The average particle size of the inorganic sol is 4 to 60 nm, preferably 10 to 40 nm. As clay-based additives, sepiolite, montmorillonite, kaolin, etc. are used.

[0070] The amount of the additive is not particularly limited, but is 50% or less, preferably 20% or less, and more preferably 10% or less, in terms of weight ratio to the zeolite. By making the weight ratio equal to or less than the upper limit, sufficient catalytic performance can be obtained. The method for mixing the mixture used in the present invention may be any method that sufficiently mixes or disperses the zeolite and the metal source, and various known methods may be used, specifically stirring, ultrasonic waves, a homogenizer, etc.

[0071] <Removal of dispersion medium> Next, the dispersion medium is removed from the mixture used in the present invention. The method for removing the dispersion medium is not particularly limited as long as it can remove the dispersion medium in a short time, but vacuum filtration, overpressure filtration, and centrifugal filtration are preferred.

[0072] After filtration, it is desirable to wash the powder with the dispersion medium several times and then dry it to completely remove the dispersion medium adhering to the powder. The drying temperature is preferably 50° C. or higher and 200° C. or lower, and more preferably 70° C. or higher and 150° C. or lower. There are no particular limitations on the atmosphere during drying, but an inert atmosphere such as air, nitrogen, or argon is preferable.

[0073] Another method for removing the dispersion medium is the spray drying method, in which the dispersion medium is removed by contacting the powder with hot air, which is a high-temperature heat medium, after the powder is uniformly sprayed. This method is preferable because it can obtain a uniform powder. When spray drying is applied in the present invention, the method of spraying that can be used includes centrifugal spraying using a rotating disk, pressurized spraying using a pressure nozzle, spraying using a two-fluid nozzle, four-fluid nozzle, or the like. The sprayed slurry is brought into contact with a heat transfer medium such as a heated metal plate or high-temperature gas to remove the dispersion medium. In either case, the temperature of the heat transfer medium is not particularly limited, but is usually 80° C. or higher and 350° C. or lower. By setting the temperature at or above the lower limit, the dispersion medium can be sufficiently removed from the slurry, and by setting the temperature at or below the upper limit, there is no possibility that the metal source will decompose and the metal oxide will aggregate.

[0074] When spray drying is used, the drying conditions are not particularly limited, but the drying is usually performed with a gas inlet temperature of about 200 to 300°C and a gas outlet temperature of about 60 to 200°C. The time required to remove the dispersion medium from the mixture in the present invention refers to the time until the amount of the dispersion medium in the mixture becomes 1% by mass or less, and the drying time when the dispersion medium is water refers to the time from the time when the temperature of the mixture becomes 80°C or higher until the amount of water contained in the mixture becomes 1% by mass or less in the obtained mixture. The drying time when the dispersion medium is other than water refers to the time from the time when the temperature becomes 20°C lower than the boiling point of the dispersion medium at normal pressure until the amount of the dispersion medium contained in the mixture becomes 1% by mass or less in the obtained mixture. The time to remove the dispersion medium is 60 minutes or less, preferably 10 minutes or less, more preferably 1 minute or less, and even more preferably 10 seconds or less. In addition, since it is desirable to dry in a shorter time, the lower limit is not particularly limited, but it is usually 0.1 seconds or more.

[0075] When the dispersion medium is removed from the mixture for a time not exceeding the upper limit, the metal source is easily supported uniformly on the surface of the zeolite on which the metal is supported, and the catalytic activity is less likely to decrease. In addition, since metal sources generally exhibit acidity or alkalinity, it is believed that when the metal source is exposed to high temperature conditions for a long period of time in the presence of a dispersion medium and containing the metal, the decomposition of the structure of the zeolite on which the metal atoms are supported is promoted. Therefore, it is believed that the longer the drying time, the lower the catalytic activity.

[0076] In addition, the average particle size of the dry powder obtained after removal of the dispersion medium is not particularly limited, but it is preferable to remove the dispersion medium so that the particle size is usually 1 mm or less, preferably 200 μm or less, and usually 2 μm or more, so that drying can be completed in a short period of time. This particle size can be determined by taking photographs of about 50 particles using an SEM, excluding extremely large particles, and measuring the circle equivalent diameter.

[0077] <Firing> After removing the dispersion medium, the obtained dry powder is calcined to obtain the catalyst of the present invention. The calcination method is not particularly limited, and a muffle furnace, a kiln, a fluidized calcination furnace, etc. can be used, but a method of calcining by circulating a gas to obtain the catalyst obtained by the present invention is preferable. The flow rate of the gas is not particularly limited, but the flow rate of the gas per 1 g of powder is usually 0.1 ml / min or more, preferably 5 ml / min or more, usually 100 ml / min or less, preferably 20 ml / min or less. The catalyst of the present invention is obtained by calcining under the flow of the gas. By setting the flow rate of the gas per 1 g of powder to be equal to or more than the lower limit, the acid remaining in the dry powder is sufficiently removed during heating, and the possibility of destroying the zeolite is reduced. By setting the flow rate to be equal to or less than the upper limit, the obtained powder is prevented from scattering.

[0078] The flowing gas is not particularly limited, but may be air, nitrogen, oxygen, helium, argon, or a mixture thereof, and is preferably air. The flowing gas may also contain water vapor. Firing in a reducing atmosphere may also be used, in which case hydrogen may be mixed into the gas, or an organic substance such as oxalic acid may be mixed into the catalyst before firing. The temperature at which the calcination is carried out in the present invention is not particularly limited, but it can be carried out usually at 250° C. or higher, preferably at 500° C. or higher, and usually at 1000° C. or lower, preferably at 900° C. or lower. By setting the temperature at or above the lower limit, the metal source is decomposed reliably, while by setting the temperature at or below the upper limit, the structure of the zeolite is unlikely to be destroyed, which is preferable.

[0079] The calcination time is from 1 second to 24 hours, preferably from 10 seconds to 8 hours, and more preferably from 30 minutes to 4 hours. After calcination, the catalyst may be pulverized. By going through the steps up to this point, the nitrogen oxide purification catalyst of the present invention can be obtained, but it is also preferable to use the nitrogen oxide purification catalyst in the form of a molded product by carrying out the following steps so as to make it easier to handle.

[0080] <Catalyst mixture> The catalyst containing the zeolite of the present invention may be used as it is in powder form, or may be mixed with a binder such as silica, alumina, or a clay mineral to form a mixture containing the catalyst (hereinafter sometimes referred to as a catalyst mixture).

[0081] In order to improve moldability and strength, various substances may be added within the range that does not deteriorate the performance. Specifically, inorganic fibers such as alumina fiber and glass fiber, clay minerals such as sepiolite, etc. may be added, and inorganic fibers such as alumina fiber and glass fiber are preferred.

[0082] <Binder> The binder contained in the catalyst mixture is usually an inorganic binder such as clay minerals such as silica, alumina, sepiolite, etc., or an organic binder. In addition, it may be a binder precursor (hereinafter), which is modified or reacted by crosslinking or the like, such as silicones, silicic acid liquid, specific silica sol or alumina sol, and exhibits a function as a binder.

[0083] Here, silicones refer to oligomers or polymers having polysiloxane bonds in the main chain, including those in which a part of the substituents in the main chain of the polysiloxane bonds has been hydrolyzed to become OH groups. Condensation reactions of silicones and silicic acid liquid proceed in a low temperature range of room temperature to about 300°C. In addition, "specific silica gel" refers to those in which condensation reactions proceed in the aforementioned temperature range.

[0084] The binder contained in the catalyst mixture is preferably, from the viewpoint of ease of molding, silicones, silicic acid liquid, specific silica sol or alumina sol, etc., which are modified or reacted by crosslinking or the like during mixing or the like to exhibit the function as a binder, and mixtures thereof. More preferably, from the viewpoint of strength during molding described below, silicones, silicic acid liquid, and mixtures thereof. Even more preferably, a compound represented by formula (I) or silicic acid liquid, and mixtures thereof.

[0085] [ka]

[0086] (In the formula (I), each R is independently an optionally substituted alkyl, aryl, alkenyl, alkynyl, alkoxy, or phenoxy; each R' is independently an optionally substituted alkyl, aryl, alkenyl, or alkynyl; and n is a number from 1 to 100.) R is preferably an alkyl group having 1 to 6 carbon atoms, an aryl group having 6 to 12 carbon atoms, an alkenyl group having 2 to 6 carbon atoms, an alkynyl group having 2 to 6 carbon atoms, an alkoxy group having 1 to 6 carbon atoms, or an aryloxy group having 6 to 12 carbon atoms, which may be optionally substituted. More preferably, R is independently an unsubstituted alkoxy group, alkyl group, or aryloxy group, and particularly preferably an alkoxy group, and among these, an ethoxy group or a methoxy group is preferable, and a methoxy group is most preferable.

[0087] R' is preferably an alkyl group having 1 to 6 carbon atoms, an aryl group having 6 to 12 carbon atoms, an alkenyl group having 2 to 6 carbon atoms, or an alkynyl group having 2 to 6 carbon atoms, which may be optionally substituted. It is preferably an unsubstituted alkyl group having 1 to 5 carbon atoms, more preferably a methyl group or an ethyl group, and most preferably a methyl group. The partial hydrolyzate of the above formula (I) is one in which at least a part of R and R' has been converted to an OH group by hydrolysis. The repeating unit n is usually 2 or more and 100 or less, preferably 2 or more and 50 or less, and more preferably 3 or more and 30 or less.

[0088] Depending on the value of n, the compounds of formula (I) exist in monomeric form or in long-chain, optionally branched, form. The silicones used in the present invention include alkyl silicates commonly known as methyl silicate and ethyl silicate. The silicic acid solution in the present invention is obtained by removing alkali metal ions from an alkali silicate solution. The method for removing the alkali metal ions is not particularly limited, but for example, a known method such as ion exchange can be adopted. For example, as described in Japanese Patent No. 3540040 and Japanese Patent Laid-Open No. 2003-26417, a method for removing the alkali metal ions by ion exchange can be adopted. + The alkali silicate can be sodium silicate, potassium silicate, or a mixture of these, but sodium silicate is preferred from the viewpoint of availability. + The cation exchange resin is a commercially available product, such as Diaion SKT-20L (manufactured by Mitsubishi Chemical Corporation) or Amberlite IR-120B (manufactured by Dow Chemical Company), which is purified by a conventional method. + The amount of cation exchange resin required to be used is selected based on publicly known knowledge, but is usually an amount that provides a cation exchange capacity equal to or greater than the amount of alkali metal ions in the alkali silicate. Ion exchange can be performed either by flow or batch, but the flow method is usually used.

[0089] SiO in silicic acid liquid 2The concentration is not particularly limited, but is usually 1 to 10% by mass, and is preferably 2 to 8% by mass in terms of strength during molding as described below. The silicic acid liquid may contain a small amount of an organic base such as an alkali metal ion, an organic amine, or a quaternary ammonium as a stabilizer. The concentration of these stabilizers is not particularly limited, but for example, the concentration of alkali metal ions in the silicic acid liquid is usually 1% by mass or less, and is preferably 0.2% by mass or less in terms of adsorption capacity, and is particularly preferably 0.0005 to 0.15% by mass.

[0090] The alkali metal ion concentration can be controlled by adding a soluble salt such as an alkali metal hydroxide, hydroxide, or sodium silicate to the silicic acid solution from which the alkali metal ions have been removed to about 100 ppm or less, or by controlling the remaining alkali metal ion concentration by adjusting the ion exchange conditions.

[0091] <Molded body> The nitrogen oxide purification catalyst or catalyst mixture of the present invention can be used after granulation or molding.

[0092] The method of granulation and molding is not particularly limited, and can be carried out using various known methods. Usually, the catalyst mixture is molded and used as a molded body. The molded body is preferably in the form of a honeycomb. When used as an exhaust gas catalyst for automobiles, etc., a honeycomb-shaped catalyst is formed by a coating method or a molding method. In the coating method, the nitrogen oxide purification catalyst of the present invention is usually mixed with an inorganic binder such as silica or alumina to prepare a slurry, which is then applied to the surface of a honeycomb made of an inorganic material such as cordierite, and then fired. In the molding method, the nitrogen oxide purification catalyst of the present invention is usually kneaded with an inorganic binder such as silica or alumina, or inorganic fibers such as alumina fiber or glass fiber, and molded by an extrusion method, compression method, or the like, followed by firing to obtain a preferably honeycomb-shaped catalyst. After the molded body is obtained, the molded body may be strengthened by applying a binder to the surface. In this case, any of the binders described above can be used as the binder, but from the viewpoint of strength during molding described below, silicones, silicic acid liquid, and mixtures thereof are more preferred, and the compound represented by formula (I) or silicic acid liquid, and mixtures thereof are even more preferred.

[0093] The molded article of the present invention is preferably produced by a process including the following three steps. (1) A first step of preparing a catalyst mixture by mixing the nitrogen oxide purification catalyst, inorganic fibers such as alumina fibers and glass fibers, and a binder. (2) A second step of extruding the catalyst mixture obtained in the first step to obtain a molded body precursor. (3) A third step of firing the molded body precursor obtained in the second step at a temperature in the range of 150° C. to 800° C.

[0094] (1st step) In the first step, at least a catalyst for purifying nitrogen oxides, inorganic fibers such as alumina fibers and glass fibers, and a binder are mixed together to prepare a catalyst mixture.

[0095] The blending ratio of the nitrogen oxide purification catalyst and binder in the catalyst mixture is usually 2 parts by weight or more and 40 parts by weight or less of the binder, calculated as the oxide, per 100 parts by weight of the nitrogen oxide purification catalyst, and preferably 5 parts by weight or more and 30 parts by weight or less in terms of the balance between strength and catalytic performance. Also, water is usually blended into the catalyst mixture. The blending ratio depends on the molding method, but is usually 10 parts by weight or more and 500 parts by weight or less based on the nitrogen oxide purification catalyst. For example, in the case of extrusion molding, the blending ratio is 10 parts by weight or more and 50 parts by weight or less based on the nitrogen oxide purification catalyst, and preferably 10 parts by weight or more and 30 parts by weight or less. Also, the catalyst mixture may be added with a plasticizer such as cellulose such as methyl cellulose, starch, polyvinyl alcohol, etc., for the purpose of increasing fluidity, depending on the characteristics during kneading and extrusion in the second step. The blending ratio is 0.1 parts by weight or more and 5 parts by weight or less based on 100 parts by weight of the nitrogen oxide purification catalyst, and preferably 0.5 parts by weight or more and 2 parts by weight or less in terms of strength.

[0096] (2nd process) In the second step, the catalyst mixture obtained in the first step is extrusion molded to obtain a molded body precursor. A known extrusion molding machine can be used for extrusion molding. Usually, the catalyst for purifying nitrogen oxides, inorganic fiber, binder, water, and optionally a plasticizer are added and kneaded, and then molded in the extrusion molding machine. There is no particular restriction on the pressure during molding, but usually it is 5 kgf / cm. 2 More than 500kgf / cm 2 After molding, the mixture is usually dried at a temperature of about 50° C. to 150° C. to obtain the desired molded body precursor.

[0097] (3rd step) In the third step, the molded body precursor obtained in the second step is fired at a temperature in the range of 150° C. or more and 900° C. or less. The temperature is preferably 200° C. or more, more preferably 250° C. or more, particularly preferably 300° C. or more, and usually preferably 800° C. or less, more preferably 700° C. or less. By firing within the above temperature range, cross-linking of the binder precursor is substantially achieved, and a molded body with high strength can be obtained.

[0098] <How to use the catalyst> The catalyst containing zeolite used in the present invention can be used as it is in powder form, or can be mixed with a binder such as silica, alumina, clay mineral, etc., and granulated or molded for use. When used as an exhaust gas catalyst for automobiles, etc., it can be molded using a coating method or a molding method, and preferably molded into a honeycomb shape for use.

[0099] When the catalyst molded body (hereinafter sometimes simply referred to as an element) obtained by the present invention is obtained by a coating method, the zeolite catalyst is usually mixed with an inorganic binder such as silica or alumina to prepare a slurry, which is then applied to the surface of a molded body made of an inorganic substance such as cordierite, and then fired. Preferably, the catalyst is applied to a honeycomb-shaped molded body to obtain a honeycomb-shaped catalyst. When the molded catalyst body obtained by the present invention is obtained by a molding method, it is usually produced by kneading zeolite with an inorganic binder such as silica or alumina, or inorganic fibers such as alumina fiber or glass fiber, molding by an extrusion method or a compression method, etc., and subsequently firing. At this time, it is preferably molded into a honeycomb shape to obtain a honeycomb-shaped element.

[0100] The catalyst of the present invention purifies nitrogen oxides by contacting exhaust gas containing nitrogen oxides. The exhaust gas may contain components other than nitrogen oxides, such as hydrocarbons, carbon monoxide, carbon dioxide, hydrogen, nitrogen, oxygen, sulfur oxides, and water. Specifically, the method of the present invention can purify nitrogen oxides contained in a wide variety of exhaust gases emitted from diesel automobiles, gasoline automobiles, various diesel engines for stationary power generation, ships, agricultural machinery, construction machinery, motorcycles, and aircraft, boilers, gas turbines, and the like. EXAMPLES

[0101] The present invention will be specifically described below with reference to examples. However, the present invention is not limited to the following examples in any way as long as the gist of the present invention is not exceeded.

[0102] [Analysis and Evaluation] The analysis of the zeolites obtained in the following examples and comparative examples was carried out by the following method. <Measurement of TG> The specifications and measurement conditions of thermogravimetric (TG) measurement are as follows.

[0103]

Table 1

[0104] <Measurement of powder XRD> (Preparation of sample) 100 mg of a zeolite sample manually pulverized using an agate mortar was set in a sample holder of the same shape so as to have a constant sample amount using the same-shaped sample holder. (Apparatus specifications and measurement conditions) The specifications and measurement conditions of the powder XRD measuring apparatus are as follows.

[0105]

Table 2

[0106] <Elemental analysis> A zeolite sample used as a standard sample was heated and dissolved in an aqueous alkali solution and an aqueous hydrofluoric acid solution, and then the Si / Al ratio and Cu / Al ratio were determined by inductively coupled plasma (ICP) optical emission spectrometry. Then, a calibration curve between the fluorescence X-ray intensity of the analytical element in the standard sample and the atomic concentration of the analytical element was created. Using this calibration curve, the zeolites obtained in each example were analyzed by X-ray fluorescence analysis (XRF), and their Si / Al ratios were determined. The ICP analysis was performed using an apparatus named iCAP7600 Duo manufactured by Thermo Fisher Scientific. The XRF was performed using a wavelength-dispersive small X-ray fluorescence analyzer: Supermini200 manufactured by Rigaku. By this method, the element ratios such as the Si / Al ratio and Cu / Al in the zeolite framework were determined.

[0107] <Measurement of FT-IR> The specifications and measurement conditions of the FT-IR are as follows.

[0108] [Table 3]

[0109] <Evaluation of catalytic activity> The catalyst samples before and after the steam treatment were press-molded, crushed, sieved, and sized to 0.6 to 1 mm. 1 ml of the sized catalyst sample was packed into an atmospheric pressure fixed-bed flow-type reactor. The catalyst layer was heated while a gas having the composition shown in Table 4 below was passed through the catalyst layer at a space velocity SV of 200,000 / h. At temperatures of 150°C, 200°C, 250°C, 300°C, 350°C, 400°C, 450°C, and 500°C, the outlet NOx (NO + NO 2 ) concentration was measured with a NOx meter, and when the outlet NOx concentration became constant, the NOx conversion rate was calculated using the following formula. NOx conversion rate (%) = {(inlet NOx concentration) - (outlet NOx concentration)} / (inlet NOx concentration) x 100 In addition, the IR spectrum of the outlet gas was measured using FT-IR to determine the N 2 The amount of O emitted was calculated using a calibration curve. 2 From the O emissions, N is calculated using the following formula: 2 The O selectivity was calculated. N 2 O selectivity (%) = 100 (%) × generated N 2 O(ppm) / (NOx conversion rate x inlet NOx)(ppm)

[0110] The calculated NOx conversion rate and N 2 The catalyst performance was evaluated before and after steam treatment based on the average O emission and selectivity.

[0111] [Table 4]

[0112] <Calculation of yield> The yield was calculated from the weight of the zeolite powder after hydrothermal synthesis and the TG measurement results using the following formula. Yield (%) = weight of recovered zeolite powder (g) × (100 (%) - H 2 O content (wt%) - OSDA content (wt%) / (total weight (g) of Si and Al in oxide equivalent other than the seed crystals in the raw material gel used in hydrothermal synthesis) H 2 O content: Weight loss rate between 30 and 200°C (wt%) OSDA content: Weight loss rate between 300 and 700℃ (wt%)

[0113] [Example 1] <Preparation of gel before hydrothermal synthesis process> 185.4g of water and amorphous Al(OH) 3 (Al 2 O 3 To the mixture was added 16.3 g of N,N-dimethyl-3,5-dimethylpiperidinium hydroxide (54.3% by weight, manufactured by Kyowa Chemical Industry Co., Ltd.), 54.9 g of a 35.2% aqueous solution of N,N-dimethyl-3,5-dimethylpiperidinium hydroxide (manufactured by Seichem Co., Ltd.) as an organic structure directing agent (OSDA), and the mixture was stirred at 300 rpm at room temperature for 15 minutes. After that, 180.3 g of Snowtex 40 (silica concentration: 40% by weight, manufactured by Nissan Chemical Industry Co., Ltd.) was added and the mixture was stirred at 300 rpm at room temperature for 1 hour to prepare slurry A-1. Aqueous solution B-1 was prepared by dissolving 16.9 g of NaOH (Kishida Chemical Co., Ltd.) in 46 g of water. The aqueous solution B-1 was added dropwise to the slurry A-1 at a rate of 1 cc / min to prepare the synthetic gel C-1. This C-1 was the raw gel. The obtained raw gel C-1 was aged at 80° C. and 300 rpm for 4 hours. Then, 5.5 g of uncalcined CHA-type zeolite (SiO 2 / Al 2 O 3 =23) was added and stirred at 300 rpm for 30 minutes at room temperature to obtain a raw gel. The molar composition ratio of the gel before hydrothermal synthesis other than the seed crystals is shown below. SiO 2 :0.071Al 2 O 3: 0.35 NaOH: 17.5 H 2 O: 0.1 OSDA

[0114] <Hydrothermal Synthesis of Zeolite> The hydrothermal synthesis pre-gel prepared by the above method was placed in a stirred tank reactor, and hydrothermal synthesis was carried out at 180 °C while stirring (60 rpm) for 25.5 hours. At this time, a stirring blade with two paddles was used in the stirred tank reactor. After the hydrothermal synthesis reaction, the reaction solution was cooled, and the crystals formed were recovered by filtration. The recovered crystals were dried at 100 °C for 12 hours to obtain Powder 1. When the XRD of the obtained Powder 1 was measured, it was confirmed that it was an AEI type zeolite. The XRD chart of this Powder 1 is shown in Figure 1. Also, the yield of the obtained AEI type zeolite was 76.8%, and the SiO 2 / Al 2 O 3 ratio (molar ratio) was 10.3.

[0115] <Firing of Zeolite> To remove the organic matter in the zeolite, the synthesized zeolite powder (Powder 1) was fired at 600 °C under an air stream for 6 hours.

[0116] <Conversion to H-Type> Next, to remove the Na ions in the fired zeolite, a zeolite dispersion was prepared from the fired zeolite and 2.7 M NH 4 NO 3 aqueous solution so that the slurry concentration calculated by the following formula was 14% by weight. Slurry concentration = zeolite powder amount (g) / (zeolite powder amount (g) + NH 4 NO 3 aqueous solution amount (g)) × 100 (wt%) Ion exchange was carried out by stirring the zeolite dispersion at 80 °C for 1 hour. The zeolite was recovered by filtration and washed 3 times with ion-exchanged water. Thereafter, the above ion exchange and three washings were repeated one more time. The obtained zeolite powder was dried at 100 °C for 12 hours to obtain NH 4 type AEI zeolite. NH in zeolite 3 To remove and convert it to the H form, the obtained NH 4 type AEI zeolite was calcined in a stream of air at 500 °C for 2 hours to obtain H-type AEI zeolite.

[0117] <Preparation of Cu-containing zeolite> Copper acetate (Cu(OAc) 2 ·H 2 O (manufactured by Kishida Chemical)) was dissolved in water to obtain a 0.05 M aqueous solution of copper(II) acetate. A dispersion prepared by mixing H-type AEI zeolite powder with this aqueous copper(II) acetate solution at a weight ratio of 10:1 was stirred at room temperature for 2 hours for ion exchange. The zeolite was recovered by filtration and washed three times with ion-exchanged water. The obtained zeolite powder was dried at 100 °C for 12 hours to obtain Cu-containing AEI zeolite. The Cu / Al of the Cu-containing AEI zeolite by XRF analysis was 0.18, and the Cu content was 2.9 wt%.

[0118] <Impregnation with Mn> 0.335 g of Mn(OAc)2·4H2O was dissolved in 33.2 g of water to obtain an aqueous solution of manganese(II) acetate. 5 g of the Cu-containing AEI zeolite was dispersed in this aqueous solution of manganese(II) acetate and stirred at room temperature for 1 hour. After stirring, all the water in the dispersion was evaporated using a rotary evaporator to impregnate all the Mn into the Cu-containing AEI zeolite. The obtained powder was calcined in air at 550 °C for 2 hours to obtain an Mn, Cu-containing AEI zeolite catalyst. In the above process, since all the Mn atoms (atomic weight 54.938) in 0.335 g of manganese acetate (molecular weight 245.09) were impregnated into 5 g of the Cu-containing zeolite, the Mn content of the obtained Mn, Cu-containing AEI zeolite catalyst is as follows. Mn content (wt%) = 0.335 g × (54.938 / 245.09) / {5 g + 0.335 g × (54.938 / 245.09)} × 100 (wt%) = 1.48 wt%

[0119] <Steam treatment of catalyst> To evaluate the catalytic activity after the hydrothermal treatment, 2.3 g of the catalyst sample was subjected to steam treatment by passing 10% by volume of steam at 800° C. and a space velocity SV of 3000 / h for 5 hours.

[0120] Regarding the Mn- and Cu-containing AEI zeolite catalyst of Example 1, the physical properties are shown in Table 5, and the catalytic activity evaluation is shown in Table 6.

[0121] [Example 2] <Preparation of raw gel> Amorphous Al(OH) in 300g water 3 (Al 2 O 3 40.4 g of colloidal silica (SiO 2 (SiO 2 416.4 g of NaOH pellets (purity 97%, Fujifilm Wako Pure Chemical Industries, Ltd.), 18.5 g of KOH pellets (purity 85%, Fujifilm Wako Pure Chemical Industries, Ltd.), and 140 g of water were mixed and stirred to dissolve, preparing a transparent solution B-2. The transparent solution B-2 was added to the slurry A-2 and mixed at room temperature for 5 minutes using a 2L scale mixer. The same procedure was repeated 87 times to prepare a raw gel.

[0122] <Preparation of gel before hydrothermal synthesis> 79.56 kg of the prepared raw gel was placed in a 100 L scale stirred tank reactor, and then aged at 80°C for 6 hours while stirring at 120 rpm using a Max Blend blade (two baffles). After aging, 10.6 kg of a 35.2% aqueous solution of N,N-dimethyl-3,5-dimethylpiperidinium hydroxide (manufactured by Seichem Co., Ltd.) was added to the mixture after aging as an organic structure directing agent (OSDA), and then 1.5 kg of water was sprinkled on it for washing. Finally, 1.4 kg of uncalcined CHA-type zeolite (Framework density: 14.5 T / 1000Å) was added as seed crystals. 3 :SiO 2 / Al 2 O 3 (= 23) was swollen in 2.5 kg of water and then mixed, and stirred at room temperature for 30 minutes to obtain a hydrothermal synthesis pre-gel. The molar composition ratios of the hydrothermal synthesis pre-gel other than the seed crystal are shown below. SiO 2 : 0.077Al 2 O 3 : 0.3NaOH: 0.1KOH: 17.5H 2 O: 0.1OSDA

[0123] <Hydrothermal Synthesis of Zeolite> The hydrothermal synthesis pre-gel prepared by the above method was subjected to hydrothermal synthesis at 180 °C with stirring (80 rpm) for 16 h. At this time, a Max Blend blade was used in the stirred tank reactor, and two baffles were used. After the hydrothermal synthesis reaction, the reaction solution was cooled, and powder 2 was recovered by filtration. The recovered powder 2 was dried at 100 °C for 12 h. When the XRD of the obtained powder 2 was measured, it was confirmed that AEI-type zeolite was synthesized. The XRD chart of powder 2 is shown in Figure 2. Note that the yield was 73.5%, and the SiO 2 / Al 2 O 3 ratio (molar ratio) was 9.7.

[0124] <Firing of Zeolite> The AEI zeolite obtained above was fired in the same manner as in Example 1.

[0125] <Conversion to H-Type> The fired AEI zeolite was converted to the H-type in the same manner as in Example 1, except that the number of repetitions of ion exchange and three washings was 4 times.

[0126] <Preparation of Cu-Containing Zeolite> From the obtained H-type AEI zeolite, Cu-containing zeolite was prepared in the same manner as in Example 1. The Cu / Al of the Cu-containing AEI zeolite by XRF analysis was 0.20, and the Cu content was 3.6 wt%.

[0127] <Impregnation with Mn> From the obtained Cu-containing AEI zeolite, a Mn, Cu-containing AEI zeolite catalyst with a Mn content of 1.48% by weight was obtained in the same manner as in Example 1.

[0128] <Steam treatment of the catalyst> Steam treatment was carried out on 2.2 g of the obtained Mn, Cu-containing AEI zeolite catalyst in the same manner as in Example 1.

[0129] For the Mn, Cu-containing AEI zeolite catalyst of Example 2, the physical properties are shown in Table 5 and the evaluation of the catalytic activity is shown in Table 6.

[0130] [Example 3] <Preparation of the raw material gel> 3474.4 g of amorphous Al(OH) 3 (Al 2 O 3 (Al, 53.5% by mass, manufactured by Kyowa Chemical Industry Co., Ltd.) was added to 25800 g of water, and 35810.4 g of colloidal silica SiO 2 (SiO 2 (SiO, 40.2% by mass, manufactured by Nissan Chemical Industries, Ltd.) was added to prepare a slurry A-3 solution. 2734.8 g of NaOH (manufactured by Fujifilm Wako Pure Chemical Corporation) and 1589.3 g of KOH (manufactured by Fujifilm Wako Pure Chemical Corporation) were mixed with 12040 g of water, stirred and dissolved to prepare a transparent solution B-3. The transparent solution B-3 was poured into the slurry A-3, and mixed at room temperature for 12 min using a high-speed stirrer on a 150 L scale (the average peripheral speed of the stirring blades is 11 m / s). The same gel mixing process was repeated 23 times in total.

[0131] <Preparation of the pre-hydrothermal synthesis gel> After putting 1555.7 kg of the prepared aqueous reactant precursor into a 2000 L scale stirred tank reactor, using a supermix impeller (with 2 baffles), while stirring at 30 rpm, aging was carried out at 80 °C for 6 h. To the aged mixture, 208.1 kg of a 35.2% aqueous solution of N,N-dimethyl-3,5-dimethylpiperidinium hydroxide (manufactured by Seikem) as an organic structure directing agent (OSDA) was added, and then 40 kg of water was sprinkled for washing. Finally, 27.6 kg of as-synthesized CHA-type zeolite (Framework density: 14.5 T / 1000 Å 3 :SiO 2 / Al 2 O 3 (SAR)=23) was swollen in 50 kg of water and then mixed, and stirred at room temperature for 30 min to obtain a raw material gel mixture. The molar composition ratio of the raw material gel mixture other than the seed crystal is shown below. SiO 2 :0.077Al 2 O 3 :0.3NaOH:0.1KOH:17.5H 2 O:0.1OSDA

[0132] <Hydrothermal synthesis of zeolite> The hydrothermal synthesis precursor gel prepared by the above method was subjected to hydrothermal synthesis for 22 h while stirring at a temperature of 180 °C (45 rpm). At this time, a supermix impeller was used in the stirred tank reactor, and 2 baffles were used. After the hydrothermal synthesis reaction, the reaction solution was cooled, and the crystals formed were recovered by filtration. The recovered crystals were dried at 100 °C for 12 h. When the XRD of the obtained powder 3 was measured, in terms of lattice plane spacing, it had peaks and relative intensities at positions as shown in Figure 3, and it was confirmed that AEI-type zeolite was synthesized. Also, the proportion of AEI-type zeolite in powder 3 was 100%.

[0133] <Firing of zeolite> The AEI zeolite obtained above was fired in the same manner as in Example 1.

[0134] <Conversion to H-type> The fired AEI zeolite was converted to the H form in the same manner as in Example 1, except that the number of repetitions of ion exchange and three washings was 4 times.

[0135] <Preparation of Cu-containing zeolite> From the obtained H-form AEI zeolite, a Cu-containing zeolite was prepared in the same manner as in Example 1. The Cu / Al of the Cu-containing AEI zeolite by XRF analysis was 0.18, and the Cu content was 3.2 wt%.

[0136] <Impregnation with Mn> From the obtained Cu-containing AEI zeolite, a Mn, Cu-containing AEI zeolite catalyst with a Mn content of 1.48 wt% was obtained in the same manner as in Example 1.

[0137] <Steam treatment of catalyst> Steam treatment was carried out on 2.2 g of the obtained Mn, Cu-containing AEI zeolite catalyst in the same manner as in Example 1.

[0138] For the Mn, Cu-containing AEI zeolite catalyst of Example 3, the physical properties are shown in Table 5 and the evaluation of the catalytic activity is shown in Table 6.

[0139] [Comparative Example 1] <Preparation of raw material gel> 2.93 g of NaOH (manufactured by Kishida Chemical) was dissolved in 10.7 g of water to prepare an NaOH aqueous solution. Then, 6.80 g of FAU zeolite (CBV720, SiO 2 / Al 2 O 3 = 30, manufactured by Zeolyst) was added, 16.2 g of a 35.2% aqueous solution of N,N-dimethyl-3,5-dimethylpiperidinium hydroxide (manufactured by Seikem) was added as an organic structure-directing agent (OSDA), 15.3 g of Snowtex 40 (silica concentration: 40 wt%, manufactured by Nissan Chemical) was added, and 0.631 g of an unfired CHA-type zeolite (SiO 2 / Al 2 O 3 = 23) was added as seed crystals, and the mixture was stirred with a magnetic stirrer at room temperature for 1 hour to obtain a raw material gel. The molar composition ratios of the raw material gel other than the seed crystal are shown below. SiO 2 :0.017Al 2 O 3 :0.35NaOH:8H 2 O:0.17OSDA

[0140] <Hydrothermal synthesis of zeolite> The raw material gel prepared by the above method was placed in a pressure-resistant container and subjected to hydrothermal synthesis for 48 hours while rotating in an oven at 175 °C (15 rpm). After this hydrothermal synthesis reaction, the reaction solution was cooled, and the crystals formed were recovered by filtration. After the recovered crystals were dried at 100 °C for 12 hours, XRD of the obtained zeolite powder 4 was measured, and it was confirmed that it was zeolite of the AEI type. The XRD chart of this zeolite powder 4 (powder 4) is shown in Figure 4. The yield of the obtained AEI zeolite was 37.9%, and the SiO 2 / Al 2 O 3 ratio (molar ratio) was 19.3.

[0141] <Firing of zeolite> 5 g of the AEI zeolite obtained above was fired in the same manner as in Example 1.

[0142] <Conversion to H-type> The fired AEI zeolite was converted to the H-type in the same manner as in Example 1.

[0143] <Preparation of Cu-containing zeolite> After preparing a Cu-containing zeolite from the obtained H-type AEI zeolite in the same manner as in Example 1, it was fired in air at 500 °C for 2 hours to obtain a Cu-containing zeolite catalyst. The Cu / Al of the Cu-containing AEI zeolite by XRF analysis was 0.31, and the Cu content was 2.9 wt%.

[0144] <Steam treatment of catalyst> The obtained Cu-containing AEI zeolite catalyst was subjected to steam treatment in the same manner as in Example 1.

[0145] For the Cu-containing AEI zeolite catalyst of Comparative Example 1, the physical properties are shown in Table 5 and the evaluation of the catalytic activity is shown in Table 6.

[0146] [Comparative Example 2] [Preparation of Raw Material Gel and Hydrothermal Synthesis of Zeolite] The raw material gel was prepared and the zeolite was hydrothermally synthesized in the same manner as in Comparative Example 1. The yield of the obtained AEI zeolite was 37.5%, and the SiO 2 / Al 2 O 3 ratio (molar ratio) was 19.7.

[0147] [Conversion to H-Type] It was converted to the H-type in the same manner as in Example 1.

[0148] [Preparation of Cu-Containing Zeolite] A Cu-containing zeolite was prepared in the same manner as in Example 1, except that a 0.10 M aqueous solution of copper(II) acetate was used, the temperature during stirring was 50 °C, and the ion exchange and washing steps were performed twice each. Then, it was calcined in air at 500 °C for 2 hours to obtain a Cu-containing zeolite catalyst. The Cu / Al of the Cu-containing AEI zeolite by XRF analysis was 0.45, and the Cu content was 4.2 wt%.

[0149] [Steam Treatment of Catalyst] The obtained Cu-containing AEI zeolite catalyst was steam-treated in the same manner as in Example 1.

[0150] For the Cu-containing AEI zeolite catalyst of Comparative Example 2, the physical properties are shown in Table 5 and the evaluation of the catalytic activity is shown in Table 6.

[0151] [Comparative Example 3] [Steam Treatment of Catalyst] The Cu-containing AEI zeolite catalyst obtained by calcining the Cu-containing AEI zeolite described in Example 1 in air at 500 °C for 2 hours was steam-treated in the same manner as in Example 1.

[0152] Regarding the Cu-containing AEI zeolite catalyst of Comparative Example 3, the physical properties are shown in Table 5, and the evaluation of the catalytic activity is shown in Table 6.

[0153] [Comparative Example 4] <Preparation of Cu-containing Zeolite> A Cu-containing zeolite catalyst was obtained by using the H-type AEI zeolite described in Example 1 and preparing the Cu-containing zeolite in the same manner as in Example 1, except that the ion exchange and washing steps were performed twice each, and then calcining at 500 °C for 2 hours in air. The Cu / Al of the Cu-containing AEI zeolite catalyst by XRF analysis was 0.29, and the Cu content was 4.7 wt%.

[0154] <Steam Treatment> The Cu-containing AEI zeolite catalyst obtained above was subjected to steam treatment in the same manner as in Example 1.

[0155] Regarding the Cu-containing AEI zeolite catalyst of Comparative Example 4, the physical properties are shown in Table 5, and the evaluation of the catalytic activity is shown in Table 6.

[0156] [Comparative Example 5] <Impregnation of Mn> Using the H-type AEI zeolite described in Example 2, Mn was impregnated in the same manner as in Example 1 to prepare a Mn-containing zeolite catalyst containing 1.48 wt% of Mn.

[0157] Regarding the Mn-containing AEI zeolite catalyst of Comparative Example 5, the physical properties are shown in Table 5, and the evaluation of the catalytic activity is shown in Table 6.

[0158] [Comparative Example 6] <Calcination of Zeolite> 5 g of CHA zeolite (SiO 2 / Al 2 O 3 = 25) was calcined in the same manner as the method described in Example 1.

[0159] <Conversion to H-type> The calcined CHA zeolite was converted to the H-type in the same manner as in Example 1.

[0160] <Preparation of Cu-containing zeolite> From the obtained H-type CHA zeolite, a Cu-containing zeolite was prepared in the same manner as in Example 1, and then calcined in air at 500 °C for 2 hours to obtain a Cu-containing zeolite catalyst. The Cu / Al of the Cu-containing CHA zeolite by XRF analysis was 0.57, and the Cu content was 4.7 wt%.

[0161] <Steam treatment> The Cu-containing CHA zeolite catalyst obtained above was steam-treated in the same manner as in Example 1.

[0162] For the Cu-containing AEI zeolite catalyst of Comparative Example 6, the physical properties are shown in Table 5, and the evaluation of the catalytic activity is shown in Table 6.

[0163]

Table 5

[0164]

Table 6

[0165] Examples 1 to 3 are SiO 2 / Al 2 O 3 ratio (molar ratio), Cu / Al, and supported amounts of Cu and Mn are in the desired ranges, and an AEI zeolite catalyst was obtained. By satisfying the above ranges, even under high-load reaction conditions such as SV = 200000 h -1 , it has high NOx purification performance while keeping the N 2 O emission amount low, and it can be seen that the degree of performance degradation is small even after the durability test, and excellent performance is maintained. Also, Examples 1 to 3 are based on the excellent catalysts as described above, with low SiO 2 / Al 2 O 3This shows that this is a cost-effective production method that can synthesize AEI zeolite with a molar ratio of 0.01 to 0.01 in high yields without using expensive Si and Al sources such as FAU, and while reducing the amount of expensive OSDA used. In contrast, in Comparative Example 1, SiO 2 / Al 2 O 3 The ratio (molar ratio) of Cu / Al is high, so it has a relatively high NOx purification performance, but 2 The amount of O emitted is high. In addition, since it does not contain Mn, the NOx purification performance is significantly reduced after durability testing. Furthermore, since FAU is used as a raw material in production, the production cost is high. In addition, in Comparative Example 2, the amount of Cu supported is larger than that in Comparative Example 1, and therefore the NOx purification performance after the durability test is improved. However, the Cu / Al ratio is increased accordingly, and therefore the NOx purification performance after the durability test is improved. 2 The amount of O discharged is increased. Furthermore, for the same reason as in Comparative Example 1, the production cost is high. In Comparative Example 3, since it does not contain Mn, the performance degradation after the durability test is significant. In Comparative Example 4, since the Cu loading amount is larger than that in Comparative Example 3, the NOx purification performance after the durability test is improved. However, since the Cu / Al ratio is large, the N 2 O emissions have increased significantly. In Comparative Example 5, since Cu was not present, the NOx purification performance was hardly observed. In Comparative Example 6, the Cu loading amount is the same as in Comparative Example 4, but the SiO 2 / Al 2 O 3 The molar ratio is high, and the Cu / Al ratio is large. Furthermore, since it does not have an AEI structure, the NOx purification performance is lower than that of Comparative Example 4. 2 The amount of O discharged is large, and the performance degradation after durability testing is remarkable. [Industrial Applicability]

[0166] The catalyst of the present invention has a high catalytic processing capacity per unit time, and can efficiently decompose and purify NOx in exhaust gas.2 N, a gas with 300 times the greenhouse effect of 2 It is an excellent catalyst that does not easily generate O. Furthermore, it has excellent durability against high temperatures, so it is highly active at high temperatures and does not undergo thermal degradation even at temperatures used to incinerate soot particles generated by incomplete combustion, making it possible to repeatedly regenerate it. Furthermore, according to the production method of the present invention, it is possible to obtain high-purity AEI zeolite or AFX zeolite on a large scale while reducing the amount of expensive organic structure-directing agent used, which is a zeolite that constitutes the above-mentioned high-performance catalyst. As described above, the nitrogen oxide purification catalyst and the method for producing the catalyst of the present invention have high NOx decomposition performance and N 2 This provides an extremely useful catalyst that suppresses O emissions and a method for producing the same, and is an industrially important technology that can contribute to industry.

Claims

1. A catalyst for purifying nitrogen oxides containing AEI type zeolite or AFX type zeolite, 2 / Al 2 O 3 %と3.5wt%。 A catalyst for purifying nitrogen oxides, comprising copper and manganese as supported metals, the amount of supported copper being 2% by weight or more and 4.5% by weight or less, the amount of supported manganese being 0.5% by weight or more and 3.5% by weight or less, and the ratio of copper to aluminum elements (Cu / Al) being 0.1 or more and 0.3 or less.

2. The method includes a mixing step of mixing at least a Si element source, an Al element source, an alkali metal element source, and water to obtain a raw material gel, an aging step of aging the raw material gel after the mixing step, a hydrothermal synthesis step, and a supporting step, The mixing step, the aging step, and the hydrothermal synthesis step are carried out in a stirred tank reactor, In the supporting step, copper and manganese are added to the AEI or AFX zeolite produced in the previous step, The ratio of the Si element source to the Al element source in the raw material gel is the molar ratio of the oxide of the Si element source to the oxide of the Al element source (SiO 2 / Al 2 O 3 (molar ratio) is 5 or more and 1000 or less, The ratio of the Si element source and the alkali metal element source contained in the raw material gel is M 2 O (M represents an alkali metal element source) molar ratio (M 2 O / SiO 2 a molar ratio of alkali metal elements to potassium elements in the raw gel is 0 or more and 0.5 or less, and a molar ratio of potassium to total alkali metal elements in the raw gel is 0 or more and 0.5 or less.

3. The raw gel further contains an alkaline earth metal element source, and the ratio of the Si element source, the alkali metal element source, and the alkaline earth metal element source contained in the raw gel is M' to the oxide of Si element. (2/n) The molar ratio (M') of O (M' represents an alkali metal element source or an alkaline earth metal element source, and n is calculated as 1 in the case of an alkali metal element source and 2 in the case of an alkaline earth metal element source) (2/n) O / SiO 2 3. The method for producing a nitrogen oxide purification catalyst according to claim 2, wherein the molar ratio of the nitrogen oxide to the nitrogen oxide is from 0.02 to 0.

5.

4. 4. The method for producing a nitrogen oxide purification catalyst according to claim 2 or 3, wherein the raw gel does not contain FAU-type zeolite but contains an organic structure-directing agent, and the ratio (molar ratio) of the organic structure-directing agent to Si atoms in the raw gel is 0.01 or more and 1 or less.

Citation Information

Patent Citations

  • Bimetallic Cu / Mn catalysts for selective catalytic reduction

    JP2021533980A